The Aide for Development , the Limits and Persepctives . Analysing the Efficacity of Aide and Rethinking About the Notion of development - Bejko, Erika (Richtmann Publishing, 2012)
The objectif of this article is to present the actual policies of Aide for Development, Public and Private Aide. Although manyefforts have been done by the whole international community to fight the poverty and and help poor countires toward their development itstill remains a challenge. At the beginning of this article I try to define and construct the concept of development trying to expose all thetheoiries od development that have influenced many actions undertaken by many international governments.Than I try to analyse thePublic Aide for the Development and its compelx and difficult functioning.. The article is a result of a systematic literature review,theoretical one but also I have consulted the annual raports edited by International Organisms suc as Mondial Banque, UNDP , UNICEFetc.. Based on the analyse of the distribution of the Public Aide for Development I constat the economic and political goals stayingbehind it.This is in a way what it is a challenge the amelioration of the efficassity of Aide. Everybody agrees that the coodnation of bothbilateral and multilateral aide should be improved in ordrer to make the one more coherent. The distribution should be also moretransparent and with the participation of the beneficiary countries. Based on the analyse and the results of this analyse I sugesst thatapart of economic methods and tools used we must work to use some innovative and new strategies taking into the consideration thevoice of civil society NGO/s and local population. It is the time to redefine the concept of development but is still remains a challenge.